THE EFFECT OF BRAND IMAGE, PRICE AND SERVICE QUALITY ON CONSUMER DECISIONS USING DELIVERY SERVICES - Nazelina, Meisya; Novitasari, Dewiana; Agung Ali Fikri, Muhamad; Asbari, Masduki (AGUSPATI Research Institute, 2020)
This study aims to determine the effect of brand image price and service quality on consumer decisions to use PT XYZ agent BP, Tangerang. This research is casual associative research which aims to determine the effect of brand image price and service quality on consumer decisions using PT XYZ agent BP, Tangerang, both partially and simultaneously. BP as the population in this study and the data used are data. primary, where data is obtained from questionnaires filled in by consumers. The analysis used is a validity test, reliability test, classical assumption test, correlation test, determination coefficient test, regression test, and hypothesis testing. Hypothesis test research results show that partially the price has a positive and significant effect on consumer decisions to use PT XYZ agent BP Tangerang, Citra Brand has a positive and significant effect on consumer decisions to use PT XYZ agent BP Tangerang, quality service has a positive and significant effect on consumer decisions to use PT XYZ agent BP Tangerang delivery services. Price, brand image, and service quality have a positive and significant effect on consumer decisions to use PT XYZ Agen BP Tangerang delivery service.